Queuing-Based Optimization of EV Charging Stations: A Case Study of Manama City, Bahrain - Albinali, Hamad A.Rahman (2025)
A Master of Science thesis in Engineering Systems Management by Hamad A. Rahman Albinali entitled, “Queuing-Based Optimization of EV Charging Stations: A Case Study of Manama City, Bahrain”, submitted in April 2025. Thesis advisor is Dr. Moncer Hariga and thesis co-advisor is Dr. Rami As'ad. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form). Embargo expires July 08, 2026.